2018
DOI: 10.24974/amae.11.3.368
|View full text |Cite
|
Sign up to set email alerts
|

Latino Faculty in Hispanic-Serving Institutions: Where is the Diversity?

Abstract: Diversity in higher education with respect to faculty composition and executive leadership remains an elusive goal for many institutions of higher education. Over thirty years of research

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 5 publications
2
21
0
Order By: Relevance
“…This argument has been further stressed by researchers who state that HSIs must provide culturally sustaining practices that promote equitable outcomes (Malcom-Piqueux & Bensimon, 2015), including culturally relevant curricula and advising practices (Garcia & Okhidoi, 2015). Elements of the organizational culture and campus climate may include the compositional diversity of the faculty (Contreras, 2017) and graduate student population, which is blatantly white when compared with the undergraduate population (Garcia & Guzman-Alvarez, 2019), while some claim that all faculty and institutional leaders must become agents of change who work toward equitable outcomes and experiences of all students at HSIs (Malcom-Piqueux & Bensimon, 2015;Garcia, 2019).…”
Section: Conceptual Framework To Understand Hsis and Servingnessmentioning
confidence: 99%
“…This argument has been further stressed by researchers who state that HSIs must provide culturally sustaining practices that promote equitable outcomes (Malcom-Piqueux & Bensimon, 2015), including culturally relevant curricula and advising practices (Garcia & Okhidoi, 2015). Elements of the organizational culture and campus climate may include the compositional diversity of the faculty (Contreras, 2017) and graduate student population, which is blatantly white when compared with the undergraduate population (Garcia & Guzman-Alvarez, 2019), while some claim that all faculty and institutional leaders must become agents of change who work toward equitable outcomes and experiences of all students at HSIs (Malcom-Piqueux & Bensimon, 2015;Garcia, 2019).…”
Section: Conceptual Framework To Understand Hsis and Servingnessmentioning
confidence: 99%
“…There is a growing body of research that focuses on faculty in HSIs. Some studies have emphasized the egregious disparities between the enrollment of Latinx undergraduates in HSIs and the employment of Latinx faculty who teach in HSIs (e.g., Contreras, 2018; Gonzales, 2015). Using data from the Integrated Postsecondary Education Data System (IPEDS), Gonzales (2015) reported that only 14.92% of the faculty at 70 HSI master’s colleges and universities across the United States self-identified as Latinx.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Raza college students have specific needs that leaders at these campuses must consider, but there are no specific models to help them become effective leaders for Raza. This is particularly troubling, as Raza are underrepresented in leadership positions at (e)HSIs (Contreras, 2018;Garcia, 2019;Gonzales, 2015;Santos & Acevedo-Gil, 2013). For example, in fall 2015 at one four-year HSI in the Midwest where 35% of the undergraduate population identified as Raza, only 11% of the faculty and 18% of the administration identified as such (Garcia, 2018b(Garcia, , 2019.…”
Section: Decolonizing Leadership Practicesmentioning
confidence: 99%
“…At another four-year HSI in the Midwest in the same year, only 2% of the faculty and 7.5% of the administration identified as Raza, compared to 27% of the undergraduate population (Garcia, 2018b(Garcia, , 2019. There has been a call to increase the representation of Raza leaders at HSIs (e.g., Contreras, 2018;Gonzales, 2015), yet in this article we call on all leaders at (e)HSIs, even non-Raza leaders, to reconsider their leadership practices in order to center Raza students. In this article, we propose processes and practices for decolonizing leadership at (e)HSIs, with the goal of promoting equitable outcomes, liberatory environments, and justice for all.…”
Section: Decolonizing Leadership Practicesmentioning
confidence: 99%
See 1 more Smart Citation